Commodification of Religion in Sport Media (Study on Bola.com Online Media) - Herman Jayadi (Publikasi Indonesia, 2025)
This study critically examines the potential for religious commodification in Bola.com sports media. sports media that actually display sports-related news are interspersed with Islamic content, the author suspects that there has been a commodification of Islam, through the online mass media Bola.com. Using a qualitative method with a netnography approach, the author has seriously analyzed several Bola.com publications during the month of Ramadan 2022, from this vulnerable time there are as many as 39 Islamic content that have been published by Bola.com on websites related to Islam. The results of the Bola.com research as an online media engaged in sports news, articles related to Islamic religious content are inseparable from the political economy motives of media and forms of media innovation for sustainability and profit, the commodification of religion in the form of content as a product in bola.com part of the media business strategy, content is an important part of the media as a selling product to get a profit for media owners. The posting of Islamic content on Bola.com also provides information that makes it easier for its readers, most of whom are Muslims, to get information related to Islam. Most of the results of this study Bola.com readers give a response that there is no problem with religious content published by Bola.com as long as the source is clear, but it is not appropriate because Bola.com is an online media of sports news which is basically only sports news and should still provide information related to sports without interfering with religious articles.